Chełmno and the Holocaust : The History of Hitler's First Death Camp - Montague, Patrick, 1954- (Book collections on Project MUSE., 2012)
"As the first extermination camp established by the Nazi regime and the prototype of the single-purpose death camps of Treblinka, Sobibor, and Belzec, the Chelmno death camp stands as a crucial but largely unexplored element of the Holocaust. This book is the first comprehensive work in any language to detail all aspects of the camp's history, organization, and operations and to remedy the dearth of information in Holocaust literature about Chelmno, which served as a template for the Nazis' 'Final Solution.' Patrick Montague reveals events leading to the establishment of the camp, how the mobile killing squad employed the world's first gas van to terminate the lives of mentally-ill patients, and the assembly-line procedure employed in the camp to commit genocide on the Jewish population. Based on over 20 years of careful research, this book provides the first single-volume history of the camp and its handful of survivors and includes previously unpublished first-hand accounts and photographs. Chelmno and the Holocaust is a vital contribution to a critically important chapter in the history of the Holocaust"--Provided by publisher.